In situ off-axis electron holography of real-time dopant diffusion in GaAs nanowires. (19th November 2022) - Balasubramanian, Ganapathi Prabhu Sai; Lebedkina, Elizaveta; Goktas, Nebile Isik; Wagner, Jakob Birkedal; Hansen, Ole; LaPierre, Ray; Semenova, Elizaveta; Mølhave, Kristian; Beleggia, Marco; Fiordaliso, Elisabetta Maria
Abstract: Off-axis electron holography was used to reveal remote doping in GaAs nanowires occurring during in situ annealing in a transmission electron microscope. Dynamic changes to the electrostatic potential caused by carbon dopant diffusion upon annealing were measured across GaAs nanowires with radial p-p+ core–shell junctions. Electrostatic potential profiles were extracted from holographic phase maps and built-in potentials ( Vbi ) and depletion layer widths (DLWs) were estimated as function of temperature over 300–873 K. Simulations in absence of remote doping predict a significant increase of Vbi and DLWs with temperature. In contrast, we measured experimentally a nearly constant Vbi and a weak increase of DLWs. Moreover, we observed the appearance of a depression in the potential profile of the core upon annealing. We attribute these deviations from the predicted behavior to carbon diffusion from the shell to the core through the nanowire sidewalls, i.e. to remote doping, becoming significant at 673 K. The DLW in the p and p+ regions are in the 10–30 nm range.